2002
DOI: 10.1172/jci200210623
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of herpes simplex virus γ134.5 expression and oncolysis of diffuse liver metastases by Myb34.5

Abstract: Myb34.5 is a herpes simplex virus 1 (HSV-1) mutant deleted in the gene for ribonucleotide reductase (ICP6). It also carries a version of γ 1 34.5 (a viral gene product that promotes the dephosphorylation of eIF-2α) that is under control of the E2F-responsive cellular B-myb promoter, rather than of its endogenous promoter. Myb34.5 replication in tumor cells results in their destruction (oncolysis). γ 1 34.5 expression by HSV-1 subverts an important cell defense mechanism against viral replication by preventing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…28 Our toxicity data using wild-type HSV-1 suggest it a suitable model. Nakamura et al assessed the safety of the ICP6 mutant hrR3 and found one of four mice died when receiving 10 8 pfu, when administered intrasplenically, 29 though the significance in toxicity observed via this route is unclear. Certainly, the administration of IV or IC rRp450, even when combined with systemic CPA (50 mg/kg), produced no adverse signs and symptoms in our studies.…”
Section: Discussionmentioning
confidence: 99%
“…28 Our toxicity data using wild-type HSV-1 suggest it a suitable model. Nakamura et al assessed the safety of the ICP6 mutant hrR3 and found one of four mice died when receiving 10 8 pfu, when administered intrasplenically, 29 though the significance in toxicity observed via this route is unclear. Certainly, the administration of IV or IC rRp450, even when combined with systemic CPA (50 mg/kg), produced no adverse signs and symptoms in our studies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Chung et al engineered Myb34.5, an HSV mutant with deletion in the gene for RR and that carries a version of ␥34.5 that is under the control of the E2F-responsive cellular B-myb promoter, rather than of its endogenous promoter (Chung et al, 1999). Compared with HSV mutants with defective ␥34.5 expression, Myb34.5 showed enhanced oncolytic efficacy against cycling cells in culture, and showed greater antineoplastic activity in mice with diffuse liver metastases from colon carcinoma (Chung et al, 1999;Nakamura et al, 2002). Kambara et al have described rQNestin34.5, an HSV mutant with deletion in the gene for RR and that carries a version of ␥34.5 that is under control of a synthetic Nestin promoter and its second intronic enhancer (Kambara et al, 2005).…”
Section: Figmentioning
confidence: 99%
“…Myb34.5 exhibits decreased virulence and toxicity in mice as compared to HSV-1 mutants with wild-type γ 1 34.5 expression. Myb34.5 infusion into the portal vein significantly lowers the hepatic tumor burden and improves survival of mice with diffuse hepatic metastases [17].…”
Section: Viral Oncolysis With Hsv-1mentioning
confidence: 99%
“…Tissue biopsies are subjected to molecular analysis such as immunohistochemical staining, polymerase chain reaction (PCR) amplification of viral DNA or RT-PCR of viral mRNA [17]. Tissue biopsy of numersous sites is invasive, cumbersome, not readily repeatable and is generally not feasible in human clinical trials.…”
Section: Pet Imaging Of Hsv-1 Oncolysismentioning
confidence: 99%